Prognostic importance of the 6 min walk test in light chain (AL) amyloidosis. Issue 20 (28th June 2022) - Cohen, Oliver C; Sathyanath, Ananth; Petrie, Aviva; Ravichandran, Sriram; Law, Steven; Manwani, Richa; Foard, Darren; Sachchithanantham, Sajitha; Mahmood, Shameem; Martinez-Naharro, Ana; Fontana, Marianna; Whelan, Carol J; et al.
Abstract : Objectives: In AL amyloidosis, organ response assessment is based on surrogates (eg, cardiac biomarkers). An objective functional test, such as the 6 min walk test (6MWT), capturing overall clinical improvement, is required. We aimed to evaluate the prognostic impact of the 6MWT at baseline and change following chemotherapy. Methods: This study evaluated the outcomes of patients who enrolled in a prospective observational study at the UK National Amyloidosis Centre (2012–2017). Patients underwent comprehensive assessments inclusive of blood testing, echocardiogram and 6MWT at baseline and annually thereafter. Results: In total, 799 patients were included within the study. Median baseline 6 min walk distance (6MWD) was 362 m (IQR: 231 m). 6MWD progressively decreased with worsening cardiac disease stage (458 m, 404 m, 331 m and 168 m for cardiac Mayo stages I, II, IIIa and IIIb, respectively (p<0.0001)). In patients with a baseline 6MWT of ≥350 m, the median overall survival was not reached (vs 30.0 (95% CI 23.2 to 36.8) months if <350 m and 5.0 (95% CI 2.8 to 7.2) months if unable to attempt 6MWT (p<0.0001). Following chemotherapy, only patients in a complete haematological response improved their 6MWD by 12 months (p=0.001). Improvement in 6MWD prolonged survival in patients with cardiac amyloidosis (p=0.005). Conclusion: The 6MWT is prognostic in AL amyloidosis. A baseline distance of ≥350 m independently predicts better survival. These data suggest that 6MWT has utility in AL amyloidosis for baseline prognosis and assessing response.